Technical expertise and behavior of the doctor- a major determinant of waiting time of OPD patients - Bansal, Cherry; Bansal, Mamta; Narang, Mandeep; Goyal, Sanjiv; Bansal, Parveen (International Journal Of Community Medicine And Public Health, 2023)
Background: The study was conducted to understand various factors affecting waiting time spent by the patients in outpatient department (OPD) and to provide recommendations for reducing the waiting time in OPD of the selected hospital. Methods: It was a descriptive cross-sectional pretested questionnaire-based study involving all new 100 consenting patients at OPD recruited into the study using a systematic sampling technique after calculating the sampling interval. Results: The study indicates that 70% of patients were satisfied and only 30% were dissatisfied with the attention given by the OPD staff, cleanliness, attentiveness of doctor but shows great dissatisfaction regarding the waiting time spent by them in the outpatient department. Most of the subjects gave the reason for their satisfaction despite more time because of expertise of the doctor, behavior of the doctor, association of hospital with non-government organizations and insurance companies for free medicine and surgery. The dissatisfaction was not because of lack of administration but because of low level of awareness amongst patients attending the OPD about internet booking of appointment, COVID protocols, priorities given to recommendations given by other doctors/VIPs and walk in OPDs attended without prior appointment. Conclusions: A very important observation which evolved from the study was the version of patients that waiting time does not matter because they want to be treated from same doctor due to his/her expertise. Second important observation was that the addressing and greeting of patient by his/her name gave a great satisfaction and level of comfort to patients and affects the waiting time.